HISTORIOGRAPHY OF RESEARCH LIFE OF ALEXANDER LAZURSKII - Leontieva, Inna V. (Educological discourse, 2015)
In this article, on the results of Study narratyvnыh sources, memuarnыh memories, the Scientific DIFFERENT articles, monographs, ocherkov, reviews, spravok in byblyohrafycheskyh Pointer, posvyaschennыh fyhurы A. Lazurskoho, vыdelenы proanalyzyrovanы and that intelligence, personality rassmatryvaly authors kotorыh scientist or kasalys different aspektov ego zhyznedeyatelnosty . Vыyasneno, something rannye byohrafycheskye personolohycheskye and Research, posvyaschennыe fyhurы A. Lazurskoho ymely Several protyvorechyvыy and volnoobraznыy, yet since the beginning of XXI century. Various aspects tvorcheskoho Heritage Alexander F. As a scientist, doctor, psychologist, teacher and active socio deyatelya all chashche stanovyatsya subject of research the Scientific researchers.